Gene delivery to therapy-relevant cells enables in vivo CAR T cell generation - Buchholz, Christian (Henry Stewart Talks, 2025)
Gene transfer vectors, Gene therapy and CAR T cells, Conventional and in vivo CAR therapy, Receptor-targeted viral vectors, Selection of DARPins for target receptors, DART-AAV vectors for immunotherapy-relevant cell types, Bispecific DARPins